Rumen fluid, a new diagnostic matrix in dairy cattle farms? (International Journal of Health, Animal Science and Food Safety, 2016)
Production diseases of dairy cows are considered man-made problems caused by the inability of cowsto achieve a sufficient feed energy intake (Mulligan, 2008).A correct management of production diseases demands early diagnostic and prognostic parameters, inorder to improve the management system and reduce the prevalence of clinical cases (Ingvartsen,2003).A previous study of our group indicated that forestomachs walls express immune receptors andcytokines, and the rumen liquor contains leukocytes able to produce IFN-γ (Trevisi, 2014).Our working hypothesis implied that ruminal fluids could be a source of diagnostic information for theidentification of herds at risk for production diseases.We first demonstrated that the diet can influence the immune response in forestomachs. Diverseleukocyte populations at low concentrations and IFN-γ were revealed in some samples of rumen fluids,with a clear inhibition of the response observed in the animals fed the maize-supplemented diet,compared to a normal and a soy-supplemented diet.We better characterized the leukocytes subpopulations in the rumen liquor, isolating B cells, monocytesand γδT cells.Finally we performed a field survey in order to find correlation among the immune profile of the rumenliquor. Clinically healthy animals showed a farm specific immunologic pattern of the rumen liquor: lowCD45 mRNA expression, low IFN-γ, few/absent B-cells.We can conclude that the epithelial cells of ruminant forestomachs can react to different stresses(metabolic, infectious, inflammatory) and the inflammatory response can be sustained by infiltratingleukocytes.Our data points into the idea that dairy farms could be ranked according to a risk score using theinflammatory markers in rumen fluids, in addition to the traditional analysis.
Keywords: Innate Immunity; Forestomachs; Inflammatory Response; Rumen